Rheological performance investigation of high viscosity liquid asphalt. Issue 12 (2nd December 2021) - Li, Jiusu; Zhu, Zhang; Ke, Li; Wang, Zhengyuan
Abstract : The bonding of asphalt and aggregate is critical especially for permeable asphalt concrete (AC) pavement and ultra-thin overlay to avoid the ravelling. High viscosity asphalt (HVA) is desirable to provide firm bonding, thereby being commonly employed both for permeable AC pavement and ultra-thin overlay. Different from the traditional hot mix asphalt (HMA) which requires significant energy consumption and accompanies pollution and aging, this paper presents a laboratory study on the rheological characteristics of HVA without heating. SBS modified asphalt was tested and prepared for liquidation and solidification using a liquefier and curing agent (CA) in an attempt to produce this high viscosity liquid asphalt (HVLA). Liquid asphalt was fabricated by adding waterborne epoxy resin emulsion (WERE) and liquid carbon petroleum resin (LCPR). The performance of the resulting HVLA was systematically evaluated. The HVLA had a Brookfield viscosity (BV), under ambient temperature of 2.42 Pa·s and an indication of acceptable workability. After solidification, penetration, softening point and ductility was 44(0.1 mm), 80°C and 18 cm, respectively. At 60°C, dynamic viscosity was 86, 450 Pa·s. Dynamic shear rheology (DSR) and bending beam rheology (BBR) gave it a performance grade of PG 82-28 with favourable workability. By analysing the results of scanning electron microscopy (SEM) and infrared spectroscopy (IR), the compatibility of the components in HLVA proved desirable.